WAYS TO IMPROVE DESIGN EDUCATION IN THE CONTEXT OF THE STRATEGY OF DIGITAL TRANSFORMATION OF EDUCATION AND SCIENCE OF UKRAINE - Chemerys , Hanna; Briantseva, Hanna; Briantsev, Olexandr (Physical and Mathematical Education, 2022)
Formulation of the problem. The article considers the digital transformation and its impact on the improvement of modern design education in higher education institutions of Ukraine. The aim of the study is to analyze the digital transformation of education in Ukraine, study the international experience of digital transformation of design education and outline ways to improve Ukrainian design education, taking into account the trend towards digital transformation.Materials and methods. To solve the tasks in the study comprehensively used general (systemic, instrumental and functional approaches, dialectical and comparative analysis, synthesis and systematization for the study of pedagogical, scientific, technical and methodological literature), special (observation and analysis of educational practice) and general methods (extrapolation). , induction and deduction to draw conclusions) of scientific research, which allowed to study the current state, evaluate the practical results of digital transformation of international design education, identify priority ways to improve Ukrainian design education in the context of digital transformation of education and science and scientifically characterize its potential.Results. The strategy of digital transformation of education and science of Ukraine provides for the improvement of design education in the following areas: influence on the selection of forms, methods and means of organizing education in the direction of virtualization of the educational process; influence on the content of educational programs of professional training of future designers; use of immersive learning technologies.Conclusions. The study confirmed that digital educational resources require students to be creative, think critically and be able to flexibly anticipate the results of design in a neoliberal economy. To improve the forms, methods and means of design education, the expediency of using LMS-platforms, webinar services, messengers, e-mail, quick testing and survey services, designers of interactive tasks is substantiated. Given the development of digital technologies in the art field and innovative activities in design practice, cloud services (such as InVision, Figma, Fusion 360, Autodesk Tinkercad, FormIt), the use of QR codes and immersive technologies such as Unity3D, virtual galleries and museums are recommended. The introduction of disruptive technologies in design practice is promising.
Keywords: digitalization; digital transformation; disruptive technologies; higher education; design education; professional training of future designers